Analysis of Metaphors in Selected Songs by Nadin Amizah Using Ullmann’s Theory - Dwi Angelica Purba; Meliala, Hanna Sartika; Simanjuntak, Yulies Pristina; Siregar, Joy Lasmita; Sitorus, Sophia Titania; Meisuri, Wiwiek (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
Metaphor is a form of figurative language that expresses meaning indirectly by comparing one concept with another concept that has similar characteristics. The purpose of this research is to identify the types of metaphors used and to analyze how metaphors are represented in the lyrics of selected songs by Nadin Amizah, namely Bertaut, Taruh, Sorai, Semua Aku Dirayakan, and Hormat Kepada Angin. This research uses Ullmann’s theory (1972) which classifies metaphors into four types: anthropomorphic metaphor, animal metaphor, concrete-to-abstract metaphor, and synesthetic metaphor. The method used in this research is descriptive qualitative. The data were collected by reading the song lyrics, identifying metaphorical expressions, and classifying them based on Ullmann’s theory. The results show that there are 20 metaphorical expressions found in the selected songs. Anthropomorphic metaphor appears most frequently with 9 occurrences (45%), followed by concrete-to-abstract metaphor with 8 occurrences (40%). Animal metaphor appears 2 times (10%), while synesthetic metaphor appears only once (5%). These metaphors are used in the lyrics to express emotional experiences and personal reflections through imaginative and figurative language.